Late mortality after vagotomy and drainage for duodenal ulcer. Issue 6427 (5th May 1984) - Watt, P C; Patterson, C C; Kennedy, T L
Abstract : Seven hundred and thirty five patients who underwent elective vagotomy and drainage procedures in one hospital during 1957-67 were followed up until 1 September 1982. At this time 281 were dead compared with an expected 184. This gives a ratio of observed to expected deaths of 1.53 (p less than 0.0001). The most important cause of increased mortality was lung cancer, which accounted for 33 of the excess deaths (observed to expected ratio 3.53). Gastric cancer yielded an observed to expected ratio of 3.3. Other causes of death that were significantly more common than expected were cerebrovascular accident, bronchopneumonia, and colorectal cancer. It is concluded that although gastric cancer occurs more commonly after vagotomy and drainage than in the general population, it is not as important a cause of death as diseases related to smoking.